Particle-based nutrients and metal contaminants in the habitat of Unionidae mussels in the Tisza River (Hungary) - Dobosy, Péter; Almeshal, Wael; Illés, Ádám; Tserendorj, Davaakhuu; Sandil, Sirat; Kovács, Zsófia; Endrédi, Anett; Záray, Gyula (Frontiers in Environmental Science, 2023)
Introduction:Unioniade is a species-rich family of freshwater mussels with an almost worldwide distribution. In Central European rivers Unio crassus, Unio tumidus and Unio pictorum have relatively high populations. In order to characterize the habitats of these suspension feeders, their nutrient supply and potential metal contaminants were investigated in near-bottom suspended (NBS) sediments and bottom sediments (BS) collected at four sampling locations along the Tisza River. Methods: The grain size distribution of sediments was determined by laser-diffraction technique. The total organic carbon (TOC) and the total Kjeldahl nitrogen (TN) were measured by a TOC analyzer and automated colorimetry, respectively. The phosphorous and metal concentrations were determined by inductively coupled plasma mass spectrometry following a microwave assisted acidic extraction of sediments with aqua regia. Results: The NBS sediments contained smaller grains than the BS samples, with roughly 85%–90% of the particles being less than 60 μm, allowing these mussels to catch them. Contrarily, only 2.47%–51.8% of BS samples were less than 60 μm. The NBS sediments contained 30, 23, and 15% more organic carbon, nitrogen, and phosphorous, respectively, than the BS samples. The rounded C:N:P molar ratios in the NBS sediments were 60:4:1, whereas they were 45:3:1 in the bottom sediments. The concentration of metals was also greater in the NBS sediments with the exception of Zn at Tokaj and Fe, Al, Mn, and Cr at Szeged, where prior contaminations transported by the tributaries Bodrog and Maros are stored in the top 10 cm of BS. Discussion: On basis of the measured C:N:P molar ratios it can be stated that soil-derived organic materials are the main sources of the nutrient elements in the habitats of suspension feeders in the Tisza River. The finer NBS sediments have higher specific surface area than the BS and thereby contain more biofilms on the grains resulting in higher proportion of organic nutrients and metal ions bounded as complexes or chelates. Comparing the measured metal concentrations of sediments with the concentration limits summarized in the Consensus-Based Sediment Quality Guidelines developed for evaluation of potential risk of metal contaminants in sediments for the benthic-dwelling organisms, it can be established that only the Hg concentration exceeded the probable effect concentration.